Development of a Bio-Battery Based on Key Lime Juice and MgSO₄ Electrolyte in a Solid Tapioca Flour Matrix - Mita, Febria; Rahmawati; Toruan, Parmin Lumban; Rahman, Dui Yanto (Jurnal Penelitian Fisika dan Terapannya (JUPITER), 2025)
Research on bio-batteries as an environmentally friendly alternative energy source continues to progress. This study aims to determine the optimal composition of key lime juice and MgSO4 that produces the maximum current and voltage. Graphite sheets are used as the anode and aluminum sheets as the cathode. The volume of key lime juice is varied at 12 ml, 14 ml, 16 ml, 18 ml, and 20 ml, then 27 g of tapioca flour is gradually added and stirred until a solid electrolyte is formed. The solid electrolyte is then placed between the graphite and aluminum sheets. The optimal composition of key lime juice is then combined with varying masses of MgSO4 at 0.1 g, 0.2 g, 0.3 g, 0.4 g, and 0.5 g to achieve higher current and voltage. Measurements show that for bio-batteries using only key lime juice as the ion source, the maximum current and voltage obtained are 1.32 mA and 0.648 V, respectively, with an optimal key lime juice volume of 16 ml. Batteries using both MgSO4 and key lime juice as ion sources produce a current and voltage of 3.72 mA and 0.720 V, respectively, with an optimal mass of 0.2 g of MgSO4. This research is very promising for further development due to its simple method and the use of inexpensive and environmentally friendly materials.